Restart Oliena 2018. Temporary strategies for a permanent regeneration - Giuseppe Boi; Barbara Camocini; Laura Daglio; Martina Mazzarello; Roberto Podda (Agathón, 2018)
Population decline in small towns in Italy and Europe has set off many explorative research efforts towards the development of new strategies for the regeneration of urban spaces. The participatory design workshop here presented faced the requalification of the semi-public courtyards, spaces representing the identity of the village of Oliena (NU), in inner Sardinia, with the aim of promoting local culture and production. The potential of these space to undergo (as rootstocks) a possible modernisation (grafting), based on contemporary living patterns and social interactions, were put at stake through activities aimed at stabilising and transforming temporary into permanent interventions, able to trigger new models of space re-appropriation.